2021
DOI: 10.37231/apj.2021.4.2.248
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Role of Technological Innovations on the Relationship Between Operational Performance and Patient Satisfaction

Abstract: The main purpose of this study is to explore the moderating role of technological innovations on the relationship between operational performance towards patient satisfaction. The study presented the first step towards a systematic and theoretical approach in understanding the patient satisfaction. To achieve this, the theory synthesizing and model approaches are adopted. Self-administrated questionnaires will be used to gather data. The findings highlighted that healthcare establishments need to focus on tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The study also found that perceived quality, trust and familiarity with the brand were important factors in the decision to purchase halal meat products. Similarly, a study by Bambale et al (2021) found that religious belief significantly influenced the intention to purchase halal meat products among Muslim consumers in Malaysia. The study also found that trust in the halal certification authority and the quality of the product were important factors in the decision to purchase halal meat products.…”
Section: Effect Of Halal Certification and Logo On Purchase Intention...mentioning
confidence: 89%
“…The study also found that perceived quality, trust and familiarity with the brand were important factors in the decision to purchase halal meat products. Similarly, a study by Bambale et al (2021) found that religious belief significantly influenced the intention to purchase halal meat products among Muslim consumers in Malaysia. The study also found that trust in the halal certification authority and the quality of the product were important factors in the decision to purchase halal meat products.…”
Section: Effect Of Halal Certification and Logo On Purchase Intention...mentioning
confidence: 89%